2010
DOI: 10.3889/mjms.1857-5773.2010.0083
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Physical Activity Program on Static Balance and Functional Autonomy in Elderly Women

Abstract: Aim. The aim of study was to assess the effects of a physical activity program on static balance and functional autonomy in elderly women. Materials and Methods.The sample was randomly divided into an experimental group (EG), submitted physical activity program, and a control (CG). Mean postural amplitude oscillations were measured in displacement from the center of pressure (COP), left lateral (LLD), right lateral (RLD), anterior (AD) posterior (PD) and elliptical (EA) areas by an electronic baropodometer. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
9
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 25 publications
(28 reference statements)
3
9
0
6
Order By: Relevance
“…Another study used adapted Tai chi program to verify the effects of targeted exercise programs on health-related quality of life compared with usual care based on the ability to perform activities of daily living (ADL) and the Neuropsychiatric Inventory scores in geriatric institutionalized persons with 65 years old above after 12 month. The components of Activity Daily Living, eg, ability to walk, continence, and nutrition, were maintained better in the intervention groups than in the control group and conclude that adapted exercise programs can slow down the decline in health-related quality of life among heterogeneous, institutionalized elderly persons [23][24][25][26][27][28]. To be active with anything is important for elderly, in this study the members of AG made domestic activities besides exercises programs.…”
Section: Discussionmentioning
confidence: 70%
“…Another study used adapted Tai chi program to verify the effects of targeted exercise programs on health-related quality of life compared with usual care based on the ability to perform activities of daily living (ADL) and the Neuropsychiatric Inventory scores in geriatric institutionalized persons with 65 years old above after 12 month. The components of Activity Daily Living, eg, ability to walk, continence, and nutrition, were maintained better in the intervention groups than in the control group and conclude that adapted exercise programs can slow down the decline in health-related quality of life among heterogeneous, institutionalized elderly persons [23][24][25][26][27][28]. To be active with anything is important for elderly, in this study the members of AG made domestic activities besides exercises programs.…”
Section: Discussionmentioning
confidence: 70%
“…Previous studies have shown the beneficial effects of physical activity on balance in elderly [31,32], after ankle instabilities or fractures [1] or on the quality of life in people with chronic diseases [33,34]. The effects of physical exercises on postural balance have been investigated by Jakobsen et al They found an improvement in postural control after 12 weeks of training [35].…”
Section: Discussionmentioning
confidence: 99%
“…The platform on which the patients stand measures the centre of pressure (COP). Most of the stabilometry protocols use stable platforms which do not describe the complexity of the balance mechanism [9,36]. The most important part of the definition states that balance is resistance against disruptions coming from both inside and outside of the body (environment changes) as well as the interaction of these two factors [4,7].…”
Section: Introductionmentioning
confidence: 99%